Exploring the molecular diversity of Eleotridae (Gobiiformes) using mitochondrial DNA. (30th January 2017) - Guimarães‐Costa, A.; Vallinoto, M.; Giarrizzo, T.; Angulo, A.; Ruiz‐Campos, G.; Schneider, H.; Sampaio, I.
Summary: Species with wide geographic distributions can consist of different lineages or even of different species. The present study evaluated the molecular diversity of the family Eleotridae by analyzing sequences of the COI gene from species collected in different locations in a Neotropical region as well as sequences from BOLD and GenBank. The analysis revealed the distinction and differentiation of a variety of species with high statistical support, including Gobiomorus dormitor (two lineages), Dormitator maculatus (three lineages) and Eleotris fusca (three lineages), and a number of different lineages of Microphilypnus . This indicates the existence of a number of unknown cryptic species that have not been reported previously, increasing the potential diversity of eleotrid species in the Neotropics.